Evaluation of influencing factors of pipeline wax deposition strength based on principal component analysis. (19th March 2023) - Xiao, Rongge; Zhuang, Qi; Jin, Shuaishuai; Liu, Bo; Liu, Guoqing
Abstract: In order to quantitatively characterize the strength of wax deposition layer in pipeline, it is very important to analyze the primary and secondary influencing factors of wax deposition layer for establishing the strength model of wax deposition layer in pipeline. Firstly, based on the experimental data of simulated wax deposit under a certain wax mixing ratio, the influencing factors of wax deposition layer strength are qualitatively analyzed. Then the principal component analysis method is introduced to quantitatively evaluate the influencing factors of wax deposition layer strength, quantify the weights of each influencing factor, and sort the influencing degree of the influencing factors. By analyzing the experimental data of simulated wax deposits with two wax mixing ratio, the results show that both the wax crystal microparameters and the solid phase wax concentration have a great influence on the strength of the wax deposition layer, and the all wax crystal microscopic parameters have greater influence on the strength of the wax deposition layer than the solid phase wax concentration. Therefore, when establishing the strength model of wax deposition layer in pipeline, it is necessary to comprehensively consider the influence of the solid phase wax concentration and the microscopic parameters of the wax crystal on it.